1900. Low Prevalence of Protective Antibodies to Measles Among Young Adults in Argentina. (26th November 2018) - Bissio, Emiliano; Biscayart, Cristián; Cisneros, Veronica; Carrega, Maria Eugenia Perez; Cassetti, Isabel; Montes, Jose Luis
Abstract: Background: In the last years, there has been an increase in incidence of cases of measles in high and middle-income countries. In Argentina, measles elimination was achieved in 2000, with no circulation of measles virus since then; vaccination iscompulsory (two doses MMR vaccine) and coverage is reported to be roughly 85%. The aim of this study was to determine seroprevalence of antibodies to measles in adults, analyzed according to HIV status. Methods: Cross-sectional study. All serologic tests requested for measles antibodies in patients aged >18 years between January 2015 and December 2017 in an Infectious Diseases Reference Center in Buenos Aires were retrieved and analyzed according to HIV status and age group. All determinations were done with VIDAS¨ Measles IgG, Biomeriex. Chi-squared and Fisher's exact tests were used for comparisons. Results: We included 2, 663 patients with determinations for measles performed in the mentioned period. Of those, 348 were HIV(+), with mean (±SD) age: 34.7(±6.2) years, 85% male (86% MSM), mean (±SD) nadir CD4 (cells/mm 3 ): 369.6(±219.5); 89% VL< 50 copies/mL; and 2, 315 were HIV(–), with mean age(±SD): 31(±5.9) years, 67% female. There was a high proportion of seronegative subjects to measles in both groups, but significantly higher in HIV+ patients (40.8% vs. 33.2%; P = 0.005). However, when analyzed by age group, in those <40 years the proportion of seronegativity to measles was higher (HIV+: 45.3% vs. 31.3%, P = 0.02; HIV-: 38.3% vs. 20.2%, P < 0.001; Figure 1). Patients older than 50 years (the most prone to having beenexposed to measles virus) had the highest prevalence of measles antibodies (>92% in both groups; Figure 2); and those younger than 40, the lowest (55% in HIV+ and 62% in HIV−). Stratification by gender did not change any of these findings. In HIV+ persons, seronegativity to measles was not associated with nadir of CD4 < 200 ( P = NS). Conclusion: We found a very high proportion of subjects without protective antibodies to measles among those <40 years (higher in HIV+ patients). This is interesting since in Argentina the vast majority of people <40 should have been vaccinated atleast once. Lack of circulation of measles might accelerate waning of antibodies. There might be an increased risk of measles in young people, especially in HIV+ persons; measures to evaluate this situation and eventually (re)vaccinate susceptiblepersons is warranted. Disclosures: E. Bissio, MSD: Employee, Salary. M. E. Perez Carrega, MSD: Employee, Salary. J. L. Montes, MSD: Employee, Salary.